ETIKA KOMUNIKASI DALAM INTERAKSI PROFESSIONAL PADA BISNIS KULINER - Thania Nadhirah Amalina; Chintia Sitohang; Hans Steven Sembiring; Marsha Rizky Nadia; Siska Amelia Maldin (JURNAL MANAJEMEN KULINER, 2025)
ABSTRACT This study aims to examine the role of communication ethics in professional interactions within the culinary business. Employing a descriptive qualitative approach through library research, the study reviews relevant literature to gain an in-depth understanding of ethical communication practices in the context of service, marketing, and workplace relations in the culinary industry. The findings reveal that communication conducted with politeness, honesty, and responsibility significantly impacts customer satisfaction, business reputation, and sustainability. In the digital era, culinary entrepreneurs are also expected to uphold communication ethics on online platforms to remain sensitive to social and cultural values. This study concludes that communication ethics serve not only as a moral guideline but also as a vital business strategy to strengthen consumer trust and competitiveness in the increasingly competitive culinary industry. Keywords: communication ethics, culinary business, professionalism.